Modifying platelets at their birth: anti-thrombotic therapy without haemorrhage - Feely, Conor; Kaushal, Nitika; D’Avino, Pier Paolo; Martin, John (Frontiers in Pharmacology, 2024)
Cardiovascular disease is a leading cause of death. The current approach to the prevention of arterial thrombosis in cardiovascular disease is dependent on the use of therapies which inhibit the activation of platelets. Predictably these are associated with an increased risk of haemorrhage which causes significant morbidity. The thrombotic potential of an activated platelet is modifiable; being determined before thrombopoiesis. Increased megakaryocyte ploidy is associated with larger and more active platelets carrying an increased risk of thrombosis. The reduction in the ploidy of megakaryocytes is therefore a novel area of therapeutic interest for reducing thrombosis. We propose a new therapeutic approach for the prevention and treatment of thrombosis by targeting the reduction in ploidy of megakaryocytes. We examine the role of a receptor mediated event causing megakaryocytes to increase ploidy, the potential for targeting the molecular mechanisms underpinning megakaryocyte endomitosis and the existence of two separate regulatory pathways to maintain haemostasis by altering the thrombotic potential of platelets as targets for novel therapeutic approaches producing haemostatically competent platelets which are not prothrombotic.